Hot Money Flows, Commodity Price Cycles, and Financial Repression in the US and the People's Republic of China: The Consequences of Near Zero US Interest Rates - Ronald McKinnon; Zhao Liu (Asian Development Bank (ADB), 2013)
Under near zero United States (US) interest rates, the international dollar standard malfunctions. Emerging markets with naturally higher interest rates are swamped with "hot money" inflows. Emerging market central banks intervene to prevent their currencies from rising precipitously. They subsequently lose monetary control and begin inflating. Primary commodity prices rise worldwide unless interrupted by an international banking crisis. This cyclical inflation on the dollar's periphery only registers in the US core consumer price index (CPI) with a long lag. The zero interest rate policy also fails to stimulate the US economy as domestic financial intermediation by banks and money market mutual funds is repressed. Because the People's Republic of China (PRC) is forced to keep its interest rates below market-clearing levels, it also suffers from "financial repression," although in a form differing from that in the US.
hdl:11540/2082
Keywords: F31; F32; 330; Dollar standard; carry trades; commodity price inflation; US-Dollar; Reservewährung; Niedrigzinspolitik; Rohstoffpreis; Inflation; Liquidität; USA; Wirkungsanalyse; China